Imide-functionalized acceptor–acceptor copolymers as efficient electron transport layers for high-performance perovskite solar cells. Issue 27 (3rd July 2020) - Shi, Yongqiang; Chen, Wei; Wu, Ziang; Wang, Yang; Sun, Weipeng; Yang, Kun; Tang, Yumin; Woo, Han Young; Zhou, Ming; Djurišić, Aleksandra B.; He, Zhubing; Guo, Xugang
Abstract : Acceptor–acceptor type copolymers are developed as electron transport layers for perovskite solar cells achieving efficiency up to 20.8% with improved device stability. Abstract : Electron transport layers (ETLs) are critical for improving device performance and stability of perovskite solar cells (PVSCs). Herein, a distannylated electron-deficient bithiophene imide (BTI-Tin) is synthesized, which enables us to access structurally novel acceptor–acceptor (A–A) type polymers. Polymerizing BTI-Tin with dibrominated naphthalene diimide (NDI-Br) and perylene diimide (PDI-Br) affords two A–A copolymers P(BTI-NDI) and P(BTI-PDI). The all-acceptor backbone yields both low-lying highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels for the polymers, which combined with their high electron mobility render P(BTI-NDI) and P(BTI-PDI) as promising ETLs for perovskite solar cells (PVSCs). When applied as ETLs to replace the conventional [6, 6]-phenyl-C61 -butyric acid methyl ester (PC61 BM) in planar p–i–n PVSCs, the PC61 BM-free devices based on P(BTI-NDI) and P(BTI-PDI) achieve remarkable power conversion efficiencies (PCEs) of 19.5% and 20.8%, respectively, with negligible hysteresis. Such performance is attributed to efficient electron extraction and reduced charge recombination. Moreover, the devices based on P(BTI-NDI) and P(BTI-PDI) ETLs show improved stability compared to the PC61 BM based ones due to the higher hydrophobicity of the new ETLs. This work provides important guidelines for designing n-type polymers to replace PC61 BM as efficient ETLs for high-performance PVSCs with improved stability.